Insights Into Mechanisms of Tumor and Immune System Interaction: Association With Wound Healing - Ponomarev, Aleksandr V.; Shubina, Irina Zh. (Frontiers in Oncology, 2019)
A large number of studies have presented a great deal of information about tumor and immune system interaction. Nevertheless, the problem of tumor evasion from the immune reaction is still difficult to resolve. Understanding the ways in which immunosuppressive tumor microenvironment develops and maintains its potential is of utmost importance to ensure the best use of the suppressed immune functions. The study presents a review covering the data on tumor-associated antigens, mechanisms of tumor evasion from the immune reactions, and search for common immunosuppressive processes of tumor growth and normal wound healing. The study discusses the important role of monocytes/macrophages in the regulation of immune system reactions. We suggest that the simultaneous actions of growth factors and pro-inflammatory cytokines may result in the suppression of the immune system. The study describes intracellular signaling molecules that take part in the regulation of the myeloid cell functions. If the hypothesis is proved correct, the indicated interaction of cytokines could be regarded as a prospective target for antitumor therapy.